Pojęcie dochodów własnych jednostek samorządu terytorialnego - Pest, Przemysław (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2015)
The Constitution of the Republic of Poland states in Art. 167 paragraph 2 that the revenues of local self-government units shall consist of their own revenues as well as general subsidies and specific grants from the State Budget. The Constitution does not define the concept of own revenues, does not indicate the criteria for determining which revenues of local self-government units should be considered its own and does not list local self-government units own revenues. The Act of 13 November 2003 on revenues of local self-government units regulates the catalogs of revenues of municipalities Art. 4, counties Art. 5 and provinces Art. 6, but also does not regulate the concept of own revenues. The absence of the legal definition of local self-government units own revenues in the Polish legal system is a condition to take in this article dogmatic legal research, with the aim to determine how to understand this concept.
Keywords: jednostki samorządu terytorialnego; gmina; powiat; województwo; dochody własne; dochody jednostek samorządu terytorialnego